BRS Reponte: high grain yield and wide adaptation wheat cultivar. - SCHEEREN, P. L. (2020)
In wheat breeding, several strategies are applied to improve grain yield. Annually, a great number of cultivars of different origins are crossed. The plants derived from these segregating populations are exposed to the most diverse possible stresses to develop new cultivars with maximum technical and economic efficiency and generate improvements to maximize the economic-environmental sustainability of plantations, while maintaining or increasing the yield potential.